2007
DOI: 10.1016/j.bbrc.2007.05.141
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of keratin intermediate filaments with sulfur mustard analogs

Abstract: Sulfur mustard (SM) is an alkylating agent with a history of use as a chemical weapon. The chemical reactivity of sulfur mustard toward both proteins and nucleic acids coupled with the hours long delay between exposure and appearance of blisters has prevented the determination of the mechanism of blister formation. We have treated assembled keratin intermediate filaments with analogs of sulfur mustard to simulate exposure to SM. We find that treatment of intact filaments with chloroethyl ethyl sulfide (CEES) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Epidermal keratins are essential for maintaining skin integrity including basal keratinocyte adhesion; mutations in epidermal keratins result in perturbation of filament assembly, which can lead to skin blistering diseases (Fuchs, 1995; Uitto et al , 2007). In vitro studies have shown that mustard vesicants induce aggregation of keratins 5 and 14; this can alter keratin filament assembly and contribute to keratinocyte detachment from the basement membrane (Dillman et al , 2003; Hess and FitzGerald, 2007). Previous studies reported a significant reduction in expression of K10 in SM treated mouse skin 3 days post exposure, and increased K10 expression in the hyperplastic epidermis 14 days post exposure (Joseph et al ,2011).…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal keratins are essential for maintaining skin integrity including basal keratinocyte adhesion; mutations in epidermal keratins result in perturbation of filament assembly, which can lead to skin blistering diseases (Fuchs, 1995; Uitto et al , 2007). In vitro studies have shown that mustard vesicants induce aggregation of keratins 5 and 14; this can alter keratin filament assembly and contribute to keratinocyte detachment from the basement membrane (Dillman et al , 2003; Hess and FitzGerald, 2007). Previous studies reported a significant reduction in expression of K10 in SM treated mouse skin 3 days post exposure, and increased K10 expression in the hyperplastic epidermis 14 days post exposure (Joseph et al ,2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite making significant contributions to the economy, leather and poultry processing industries cause severe environmental pollution owing to the use of various chemicals and the release of a variety of detrimental materials. Therefore, in poultry farm feathers are often converted to feather-meal through steam pressure and chemical treatment [8] that have disadvantage of destroying several important amino acids [9]. In leather processing industry, the first step is to remove hairs from hides and skins.…”
Section: Introductionmentioning
confidence: 99%
“…For example, skin keratins are prone to modification by alkylating agents such as sulphur mustard. The interactions of the analogs of sulphur mustards such as chloroethyl ethyl sulfide and mechlorethamine (also known as nitrogen mustard) with the keratin intermediate filament, showed keratin filament destruction, leading to lysis of epidermal basal cells and skin blistering 90 . A study is reported on using model peptides containing cysteine, lysine and histidine residues to predict the interaction mechanisms of the nitrogen mustards (mechloroethamine and tris-2-chlorethylamine) to amino acid residues of proteins by means of liquid chromatographytandem mass spectrometry.…”
Section: Interaction Of Keratin With Chemical Warfare Agentsmentioning
confidence: 99%